PERBEDAAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL ARTIKULASI DENGAN MODEL KONVENSIONAL SISWA SMP NEGERI 18 MERANGIN - Ade Susanti; Susiana (Pendidikan Matematika | STKIP YM Bangko, 2017)
The low mathematics learning outcomes obtained by students become a problem faced in mathematics learning. To overcome this problem, the teacher is expected to be able to choose the right learning model in the classroom so that the expected goals in the learning process can be achieved. This study aims to look at differences in the cooperative model of articulation type with conventional models on Mathematics learning outcomes. This study is a comparative study with the population is all students of class VII of SMP N 18 Merangin. The technique of collecting data using tests was analyzed using the t-test. Based on the results of the analysis, it was found that there was a difference between the cooperative model of articulation type and the conventional model of the learning outcomes of mathematics. Student learning outcomes taught with cooperative models of articulation type are better than conventional models. Keywords: Cooperative Learning, Articulation Model, Learning Outcomes